2021
DOI: 10.1049/itr2.12158
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic driving intention recognition of vehicles with different driving styles of surrounding vehicles

Abstract: Driving behaviour of surrounding vehicles have impacts on the security of ego vehicle. However, many vehicles do not use the turn signal in advance as a warning when changing lanes, which often leads to traffic accidents. Therefore, in the case of Internet of Vehicles (IoV) technology has not been popularized, recognizing the driving intention of surrounding vehicles timely and accurately through effective method is of great significance to ego vehicle. In this paper, a dynamic driving intention recognition me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…For instance, Wang et al [30] analysed the different pattern of on-ramp behaviours, and revealed how decision-making is influenced by vehicles' social preference. Zhang et al [31] focused on lane change in highways, and provided insights to the driving styles. Through studying the conflict process, interaction mechanisms are revealed, behaviour semantics are classified.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, Wang et al [30] analysed the different pattern of on-ramp behaviours, and revealed how decision-making is influenced by vehicles' social preference. Zhang et al [31] focused on lane change in highways, and provided insights to the driving styles. Through studying the conflict process, interaction mechanisms are revealed, behaviour semantics are classified.…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al. [31] focused on lane change in highways, and provided insights to the driving styles. Through studying the conflict process, interaction mechanisms are revealed, behaviour semantics are classified.…”
Section: Introductionmentioning
confidence: 99%